2012
DOI: 10.1016/j.pain.2012.05.008
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI study on the acute effects of exercise on pain processing in trained athletes

Abstract: Endurance exercise is known to promote sustained antinociceptive effects, and there is evidence that the reduction of pain perception mediated by exercise is driven by central opioidergic neurotransmission. To directly investigate the involved brain areas and the underlying neural mechanisms in humans, thermal heat-pain challenges were applied to 20 athletes during 4 separate functional magnetic resonance imaging (fMRI) scans, i.e., before and after 2 hours of running (exercise condition) and walking (control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 55 publications
2
53
1
1
Order By: Relevance
“…We can only speculate about possible mechanisms of exercise in migraine. On the one hand, the exercise may reduce the pain perception through activation of opioidergic system [52]. This could have been the case, because the exercise in our study influenced the migraine duration more than the frequency of migraine.…”
Section: Discussionmentioning
confidence: 89%
“…We can only speculate about possible mechanisms of exercise in migraine. On the one hand, the exercise may reduce the pain perception through activation of opioidergic system [52]. This could have been the case, because the exercise in our study influenced the migraine duration more than the frequency of migraine.…”
Section: Discussionmentioning
confidence: 89%
“…The pain reduction in the E group, despite increased joint loads, inflammation, and walk speed, may indicate psycho-physiological effects of exercise on the central 34 and peripheral nervous systems. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that intense exercise is followed by an increase in heat-pain thresholds, a phenomenon termed "exercise induced analgesia" (EIA; Scheef et al, 2012;Koltyn, Brellenthin, Cook, Sehgal, & Hillard, 2014;Crombie, Brellenthin, Hillard, & Koltyn, 2017). Although EIA lasts up to 30 min (Hoffman et al, 2004), perhaps its effects are cumulative, namely the EIA of athletes is constantly on an "on" mode, whereas it has an "on" and "off" modes among non-athletes, depending on the frequency/intensity of their exercises.…”
Section: Basal Pain Perception Of Athletesmentioning
confidence: 99%
“…Studies have shown the reinforcement of CPM during distraction (Defrin, Tsedek, Lugasi, Moriles, & Urca, 2010;Droste, Greenlee, Schreck, & Roskamm, 1991;Lautenbacher, Prager, & Rollman, 2007), a state reported frequently by endurance athletes, especially triathletes. Endurance athletes also report euphoria following training, which correlated with pain threshold and endogenous opioids increase (Boecker et al, 2008;Droste et al, 1991) as well as with brain activation in pain modulation regions (Boecker et al, 2008;Scheef et al, 2012). Thus, endurance athletes may have greater potential than strength athletes, for top-down pain modulation enhancement.…”
Section: The Effects Of the Type Of Sport On Pain Perception And Momentioning
confidence: 99%